2014
DOI: 10.1021/cb500678c
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acids as Probes for Investigation of Allosteric Modulation of the Chemokine Receptor CXCR3

Abstract: The chemokine receptor CXCR3 is a G protein-coupled receptor, which conveys extracellular signals into cells by changing its conformation upon agonist binding. To facilitate the mechanistic understanding of allosteric modulation of CXCR3, we combined computational modeling with the synthesis of novel chemical tools containing boronic acid moiety, site-directed mutagenesis, and detailed functional characterization. The design of boronic acid derivatives was based on the predictions from homology modeling and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 55 publications
6
46
0
Order By: Relevance
“…Importantly, even if these assumptions did not hold entirely true for all the novel allosteric modulators, this analysis enables a first approximation and a semi-empirical estimate of cooperativity. 51 The data from functional studies, where discrete concentrations of agonists were used, were fitted to the following equations using Prism 5.0:…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, even if these assumptions did not hold entirely true for all the novel allosteric modulators, this analysis enables a first approximation and a semi-empirical estimate of cooperativity. 51 The data from functional studies, where discrete concentrations of agonists were used, were fitted to the following equations using Prism 5.0:…”
Section: Resultsmentioning
confidence: 99%
“…We tentatively speculate that psychosine behaves as an orthosteric antagonist and that the imidazopyridine compound behaves as a negative allosteric modulator [38] of GPR4. As an example of the negative allosteric modulator, a recent study has shown that boronic acid derivatives for chemokine receptor CXCR3 act on second allosteric binding pocket of the receptor to modulate receptor functions [39]. …”
Section: Discussionmentioning
confidence: 99%
“…For CXCR3, two nonpeptidic small-molecule ligands were reported as biased allosteric agonists of the receptor, as they recruit b-arrestin with greater efficacy than the endogenous agonist. [32] Another important aspect of allosteric modulation of chemokine receptors is probe dependence. [30] From a pharmacological perspective, an agonist can not only elicit biased signaling, but antagonists can also act permissively.…”
Section: Introductionmentioning
confidence: 99%